ANALYSIS OF PRODUCTION NETWORK USING ECONOMIC INDICATORS METHODS (Marketing Journal, 2025)
This article examines the analysis of a production network using economic indicators as an effective tool for enterprise management. Key methods, including economic and mathematical modeling, comparative and cluster analysis, as well as their application t o improve productivity and reduce costs are analyzed. Based on the study, recommendations are proposed for the implementation of digital technologies, standardization of methods and strengthening of interaction between departments. The 553 use of these approaches helps to increase the sustainability and competitiveness of production networks in the conditions of the modern economy.
Keywords: production network analysis; economic indicators; economic and mathematical modeling; comparative analysis; cluster analysis; productivity; cost optimization; sustainable development; digitalization